Positive Internal Experiences in PTSD Interventions: A Critical Review. (January 2022) - Contractor, Ateka A.; Weiss, Nicole H.; Forkus, Shannon R.; Keegan, Fallon
Evidence suggests that individuals with post-traumatic stress disorder (PTSD) symptoms exhibit deficits in positive internal experiences. This study critically reviewed empirically validated PTSD interventions to determine (1) whether positive memories, cognitions, and emotions were explicitly addressed and (2) the goals of focusing on these positive internal experiences. We selected 11 empirically validated PTSD interventions listed as "recommended/strongly recommended" in recently published reviews, reviewed existing literature for studies using these interventions ( N = 1, 070), short-listed randomized controlled trial studies meeting predetermined inclusion criteria for the selected interventions (in English, developed for adults, individual therapy modality, in-person administration, tailored to PTSD; N = 47), and emailed authors ( N = 41) to obtain the unique intervention manuals. Hereby, we reviewed 13 unique empirically validated PTSD intervention manuals. Findings indicated 53.85%, 69.23%, and 69.23% of reviewed manuals explicitly discussed positive memories, emotions, and cognitions, respectively. Primarily, positive memories were integral to mechanisms underlying PTSD, a precursor to targeting negative experiences, an indicator of treatment progress, or a way to identify client problems; positive emotions were discussed when providing psychoeducation on PTSD/trauma reactions; and positive cognitions were addressed in reference to coping with negative experiences or as targets to enhance self-concept. This review demonstrates that comparatively, positive memories are infrequently elicited in the reviewed interventions; positive emotions and cognitions are explicitly referenced in two-thirds of the reviewed interventions but are included as a primary focus for therapeutic processing only in a few interventions; and eye movement desensitization and reprocessing has the most comprehensive focus on positive internal experiences.